1997
DOI: 10.1021/ac970696n
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Critical Micelle Concentration Values Using Capillary Electrophoresis Instrumentation

Abstract: The purpose of this work is to demonstrate the usefulness of capillary electrophoresis (CE) instrumentation for determining values of critical micelle concentration (cmc) of surfactants. The approach essentially consists of a CE version of the traditional method of measuring values of cmc by conductivity. Namely, the different conductivities of ionic surfactants in solution depending on their aggregation state, i.e., as monomers or micelles, and the effect on the electrical current as usually measured in a CE … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
154
1
1

Year Published

2000
2000
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 233 publications
(171 citation statements)
references
References 25 publications
15
154
1
1
Order By: Relevance
“…As outlined in Table 1a, the CMC of pure SDS (empty squares) is 7.9 mM which agrees well with earlier reported data [30][31][32]. In the presence of 0.5 wt% of the polymer, the CMC of SDS is lowered significantly from 7.9 mM to 1.2 mM, such decrease in the CMC could be understood as the aggregation of the SDS on the polymer.…”
Section: Resultssupporting
confidence: 90%
“…As outlined in Table 1a, the CMC of pure SDS (empty squares) is 7.9 mM which agrees well with earlier reported data [30][31][32]. In the presence of 0.5 wt% of the polymer, the CMC of SDS is lowered significantly from 7.9 mM to 1.2 mM, such decrease in the CMC could be understood as the aggregation of the SDS on the polymer.…”
Section: Resultssupporting
confidence: 90%
“…The SDS concentration in our report was higher than its CMC. From experiment, it showed that CMC of SDS surfactant is around 8.1-8.4 mM (equivalent to 0.23 wt %) [35]. In our DPD calculation, CMC of surfactant was determined by counting the number of free molecules in the solution.…”
Section: Computational Detailsmentioning
confidence: 99%
“…It is well known that surfactant molecules are associated with micelles which begin to form above the critical micellar concentration (CMC) [19][20][21][22]. Numerous factors such as the addition of electrolytes [23][24][25], the pH of the buffer [26], the temperature [27,28], the addition of organic modifiers [29,30] Ionic strength of the aqueous solution [31,32], the presence of additives etc., make this value different from that determined in pure water.The determination of the CMC takes place in several ways such as the tensiometry which records the decrease in the surface tension as a function of the surfactant concentrations up to a limit beyond which the surface tension no longer decreases, and other methods used as conductivity [33][34] for charged surfactants, spectrofluorometry, nuclear magnetic resonance and UV-visible absorption spectroscopy [35][36][37].In the present work, we describe the synthesis of a new surfactant monomer derived from 5-Chloroisatin via the N-alkylation method under the conditions of phase transfer catalysis followed by the quaternizationof 1-(6-bromohexyl) 5 …”
Section: Introductionmentioning
confidence: 99%